Patterns of foreign exchange intervention under inflation targeting - Gustavo Adler (Elsevier, 2021)
The paper documents the use of foreign exchange intervention (FXI) across countries and monetary regimes, with special attention to its use under inflation targeting (IT). We find significant differences between advanced (AEs) and emerging market economies (EMEs). The former group conduct FXI limitedly and broadly symmetrically, while the use of this policy instrument in EMEs is pervasive and mostly asymmetric, with a bias toward purchasing foreign currency, even after taking precautionary motives into account. Within emerging markets, the use of FXI is common under both IT and non-IT regimes. We find no evidence of FXI being used in response to inflation developments, while strong evidence exists that FXI responds to exchange rate movements, indicating that IT central banks in EMEs have dual inflation/exchange-rate objectives. We also find a higher propensity to overshoot inflation targets in emerging market economies in which FXI is more pervasive.